Occupational exposures to electromagnetic fields in the INTEROCC study. (19th October 2011) - Kincl, Laurel; Bowman, Joseph; Conover, David; Guo, Yixuan; Figuerola, Jordi; McLean, David; Richardson, Lesley; van Tongeren, Martie; Cardis, Elisabeth
Abstract : Objectives: to assess workplace exposures to electric and magnetic fields (EMF) at radio frequencies (RF) and extremely low frequencies (ELF); to estimate brain cancer risks from occupational ELF magnetic fields. Methods: Personal interviews of INTEROCC subjects included lifetime occupational histories and detailed questions about workplace EMF sources. To evaluate EMF exposures, personal ELF magnetic field monitoring data were compiled into a job-exposure matrix (JEM), and source measurements were assembled into a source-exposure matrix (SEM). Algorithms were developed for combining the JEM and SEM with interview data to calculate cumulative EMF magnitudes in the RF and ELF bands for all subjects. As the first step in our EMF risk analyses, cumulative exposures to ELF magnetic fields were calculated from the JEM, and used to assess risks for meningioma and glioma, adjusting for age, gender, region, and education. Results: The SEM has EMF exposures for all 188 RF sources reported by INTEROCC subjects, and the JEM has ELF magnetic fields for all their 561 jobs. Initial analyses with ELF suggested no associations with glioma (OR=0.83 in the highest quintile, 95% CI: 0.64 to 1.04) or meningioma (OR=0.99 in the highest quintile, 95% CI: 0.78 to 1.26). Conclusions: The risk analysis with the ELF JEM is the first step in INTEROCC's EMF protocol, and shows no association. When individualised exposure assessments using the interview reports on EMF sources and usage conditions are completed, INTEROCC with its 8948 subjects will be the most powerful study of occupational EMF and brain cancer ever conducted.